Preoperative Neutrophil Lymphocyte Ratio Can Be Used as a Predictor of Prognosis in Patients With Adenocarcinoma of the Esophagogastric Junction: A Systematic Review and Meta Analysis - Liu, Xiao-bo; Gao, Zi-ye; Zhang, Qing-hui; Pandey, Sandeep; Gao, Bo; Yang, Fan; Tong, Qiang; Li, Sheng-bao (Frontiers in Oncology, 2020)
Objective: NLR, LMR and PLR can be used as various prognostic factors for malignant tumors, but the value of prognosis for patients with adenocarcinoma of the esophagogastric junction (AEG) has not been determined. This study used meta-analysis to assess the value of these indicators in the evaluation of AEG prognosis. Methods: Relevant literatures on the prognostic relationship between NLR, LMR, PLR and AEG was retrieved from PubMed, Web of Science, Embase, Cochrane Library, Cochrane Central Register of Controlled Trials, Wanfang data and Chinese National Knowledge Infrastructure. The search time from database establishment to June 30, 2019. The language is limited to English and Chinese. Data was analyzed using Stata 15.0 software. Result: Six retrospective studies were included, five of them involved NLR and six of them involved PLR. No LMR literature that adequately satisfied the conditions was retrieved. Increased NLR was significantly associated with a significant reduction in overall survival (OS), cancer-specific survival (CSS), or disease specific survival (DSS) in patients with AEG (HR = 1.545,95% CI: 1.096 2.179, P<0.05). Subgroup analysis showed that NLR had significant value in the prognosis of both Chinese and Non-Chinese patients (P=0.009 VS. P=0.000). NLR had significant prognostic value for ≥3 and <3 groups (P=0.022 VS. P=0.000). NLR has a significant prognostic value for samples ≥ 500 and < 500 (P = 0.000 VS. P = 0.022). NLR and OS/CSS/DSS single factor meta-regression showed that regional NLR cut-off values and sample size may be the source of heterogeneity in AEG patients (all P < 0.05). There was no significant association between elevated PLR and OS in patients with AEG (HR=1.117, 95% CI: 0.960 1.300, P>0.05). PLR had no significant prognostic value for both Chinese and UK patients (P=0.282 VS. P=0.429). PLR had no significant prognostic value for ≥150 group and <150 group (P=0.141 and P=0.724). No significant prognostic value was found in either the 300 group and <300 group (P=0.282 VS. P=0.429). Conclusion: Preoperative NLR rise was an adverse prognostic indicator of AEG. High-risk patients should be treated promptly. The results showed that PLR was not recommended as a prognostic indicator of AEG.